The Deep Learning Approach to Improve Learning Interest in Cultural Heritage Material at Private Elementary School - Lala Sentia Lesnussa; Ode Abdurrachman; Leonid Ritiauw (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Learning about cultural heritage in elementary schools is often less popular due to the presentation being theoretical and less relevant to the students' life context. This study aims to test the effectiveness of the deep learning approach in increasing the learning interest of fifth-grade students at Fena Fafan Private Elementary School 12 in this material. Using a quantitative method with a pre-experimental design (one-group pretest-posttest), this study involved 19 students as a sample. Data were analyzed statistically using a paired t-test and the N-Gain test. The results showed that the deep learning approach significantly increased students' interest and learning outcomes. This was evidenced by the results of the hypothesis test, which showed a significant difference between the pretest and posttest scores (p = 0.000), as well as the N-Gain score of 0.74, which was included in the High category. The implementation of the principles of mindfulness, meaningful, and joyful learning successfully shifted the learning paradigm to be student-centered and created an interactive classroom atmosphere. In addition to increasing motivation and enthusiasm, this approach proved effective in developing 21st-century skills (4Cs) by contextual media and the involvement of local partners. This research provides practical contributions for educators in adopting alternative strategies that can transform theoretical material into in-depth and enjoyable learning experiences.